A Biomechanical Study of Posteromedial Tibial Plateau Fracture Stability: Do They All Require Fixation?. Issue 7 (July 2015) - Cuéllar, Vanessa G.; Martinez, Danny; Immerman, Igor; Oh, Cheongeun; Walker, Peter S.; Egol, Kenneth A.
Abstract : Objectives: Although the posteromedial fragment in tibial plateau fractures is often considered unstable, biomechanical evidence supporting this view is lacking. We aimed to evaluate the stability of the fragment in a cadaver model. Our hypothesis was that under the expected small axial force during rehabilitation and the combined effects of this force with shear force, internal rotation torque, and varus moment, the most common posteromedial tibial fragment morphology could maintain stability in early flexion. Methods: Axial compression force alone or combined with posterior shear, internal rotation torque, or varus moment was applied to the femurs of 5 fresh cadaveric knees. A Tekscan pressure mapping system was used to measure pressure and contact area between the femoral condyles, meniscus, and tibial plateau. A Microscribe 3D digitizer was used to define the 3-dimensional positions of the femur and tibia. A 10-mm and then a 20-mm osteotomy was created with a saw at an angle of 30 degrees in the axial plane with respect to the tangent of the posterior tibial plateau and 75 degrees in the sagittal plane, representing a typical posteromedial fracture fragment. At each flexion angle (15, 30, 60, 90, and 120 degrees) and loading condition (axial compression only, compression with shear force, torque, and varus moment), distal displacement of the medial femoral condyle and the tibial fracture fragments was determined. Results: For the 10-mm fragment, medial femoral condyle displacement was little affected up to approximately 30-degree flexion, after which it increased. For the 20-mm fragment, there was progressive medial femoral condyle displacement with increasing flexion from baseline. However, for the 10- and 20-mm fragments themselves, displacements were noted at every flexion angle, starting at 1.7 mm inferior displacement with 15 degrees of flexion and internal rotation torque and up to 10.2 mm displacement with 90 degrees of flexion and varus bending moment. Conclusions: In this cadaveric model of a posteromedial tibial plateau fracture, both fracture fragments studied displaced with knee flexion, even at low flexion angles. Although such fragments may initially seem nondisplaced after injury, posteromedial fragments similar to these tested are likely to displace during knee range of motion exercises in non-weight-bearing conditions. Abstract : Supplemental Digital Content is Available in the Text.